Exploring self-rated health, physical activity, and social anxiety among female Chinese university students: a variable- and person-centered analysis - Huang, Wenying; Chen, Bin; Hu, Chang (Frontiers in Public Health, 2025)
BackgroundPhysical inactivity is a significant public health issue among female college students. This study aimed to explore the complex relationship between self-rated health (SRH), social anxiety (SA), and physical activity (PA) in a sample of female Chinese university students, employing both variable-centered and person-centered approaches.MethodsA cross-sectional survey was conducted with a sample of 1,452 female Chinese university students who completed the Self-Perceived Health Scale (to measure SRH), the Social Interaction Anxiety Scale–6 and the Social Phobia Scale–6 (to measure SA), and a validated single-item measure of PA (to measure PA). First, a mediation model was used to test the indirect effect of SRH on PA through SA. Second, Latent Profile Analysis was conducted to identify distinct subgroups based on individuals’ SRH and SA levels. Finally, ANOVA was used to examine PA differences across the identified profiles.ResultsThe mediation analysis revealed that SA partially mediated the relationship between SRH and PA, accounting for 12% of the total effect (CI [0.011, 0.090]). The Latent Profile Analysis identified three distinct profiles: “Healthy-Resilient” (21.62%), characterized by high SRH and low SA; “Moderate-Adapting” (70.39%), with average SRH and SA; and “Unhealthy-Anxious” (7.99%), with low SRH and high SA. The “Unhealthy-Anxious” group reported significantly lower levels of PA than the other two groups.ConclusionOur findings suggest that SA is a significant psychological mechanism linking SRH to PA among female Chinese university students. From a public health perspective, these findings highlight the importance of addressing mental health factors, such as SA, in interventions designed to promote PA in this population. The identification of distinct subgroups underscores the need for tailored interventions over one-size-fits-all approaches.